Big data analytics in chemoinformatics and bioinformatics : with applications to computer-aided drug design, cancer biology, emerging pathogens and computational toxicology - Basak, Subhash C., 1945-; Vracko, Marjan (Elsevier, 2023)
"Big Data Analytics in Chemoinformatics and Bioinformatics provides an up-to-date presentation of big data analytics methods and their applications in diverse fields. Various aspects of science, technology, and health care are affected by big data and associated prediction tools. The proper management of big data for decision-making in scientific and social issues is of paramount importance. This book gives researchers the tools they need to solve big data problems in these fields. The book begins with a section on general topics that all readers will find useful, and it continues with specific sections covering a range of interdisciplinary applications. An international team of leading experts review their respective fields and present their own latest research findings, and case studies which are utilized throughout to analyze and present key information."--Page 4 of cover.